2017
DOI: 10.1002/pmh.1375
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and self‐injurious behaviours in adolescent and adult patients with borderline personality disorder

Abstract: Objective Prevalence data on self-mutilation and suicide attempts for adolescent borderline personality disorder (BPD) is currently not available. The purpose of this paper was to determine the frequency and methods of two forms of physically self-destructive acts (i.e., self-mutilation and suicide attempts) reported by adolescent borderline inpatients in one of the largest samples to date and to compare these results with a similarly diagnosed and assessed group of adult borderline inpatients. Methods A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 23 publications
4
62
1
4
Order By: Relevance
“…For people diagnosed with BPD, DBT is one of the few evidence-based treatments which has been found to reduce hospitalisation, use of crisis services, and improve quality of life, even in modest studies in naturalistic settings . Untreated or ineffectually treated BPD often leads to escalations of self-injurious behaviour, use of crisis services and completed suicide (Goodman et al, 2017). Although, a recent review suggests that if people remain engaged with 'treatment as usual', then some stability or modest gains can be demonstrated (Finch et al, 2019).…”
mentioning
confidence: 99%
“…For people diagnosed with BPD, DBT is one of the few evidence-based treatments which has been found to reduce hospitalisation, use of crisis services, and improve quality of life, even in modest studies in naturalistic settings . Untreated or ineffectually treated BPD often leads to escalations of self-injurious behaviour, use of crisis services and completed suicide (Goodman et al, 2017). Although, a recent review suggests that if people remain engaged with 'treatment as usual', then some stability or modest gains can be demonstrated (Finch et al, 2019).…”
mentioning
confidence: 99%
“…Among inpatients with BPD, 90% endorse history of self-injury and more than 70% endorse history of suicide attempt(s) (Goodman et al, 2017). Other studies in adult samples have also found high rates of suicidal ideation and attempts among people with BPD (Wedig, Between 5-10% complete suicide (Black, Blum, Pfohl, & Hale, 2004;Paris, 2006) (Pompili et al, 2005).…”
Section: Self-harmmentioning
confidence: 93%
“…For those with BPD, suicide and self-harm are particular risk factors affecting morbidity and mortality. For example, Goodman, Tomas, Temes et al (2017) found in a sample of 104 adolescents and 290 adults with a diagnosis of BPD that 90 percent engaged in self-mutilation and 75 percent had made multiple suicide attempts. Further, clients with BPD have been shown to complete suicide 50 times high than the general population (APA, 2001).…”
Section: Impact Of Borderline Personality Disordersmentioning
confidence: 99%